The General Factor of Personality as Ego-Resiliency - Dunkel, Curtis S.; van der Linden, Dimitri; Kawamoto, Tetsuya; Oshio, Atsushi (Frontiers in Psychology, 2021)
It was originally hypothesized by Block (1965) that what has come to be known as the General Factor of Personality (GFP) reflects ego-resiliency. We test Block’s hypothesis in two studies. In Study 1 a meta-analysis (N = 15,609) examining the relationship between the GFP and ego-resiliency/resilience was conducted. In Study 2 (N = 157) archival data for the Block and Block (2006a) was used to examine the association between rater judged ego-resiliency across childhood, adolescence, and into early adulthood and the GFP based on self-report in early adulthood. Using structural equation modeling for the meta-analytic data, the correlation between the GFP and ego-resiliency/resilience was estimated at r = .93. Using a trait-state occasion model to test the hypothesis in Study 2, the correlation between the GFP and rated ego-resiliency was estimated at r = .85. The results of the two studies offer substantial support for Block’s original hypothesis. Given the strength of the associations between the GFP and ego-resiliency/resilience one may conclude that the two constructs largely reflect the same underlying phenomenon.